Assessing the mobility of Zn, Pb and Ni during the weathering of Nkana smelter copper slag, Zambia - Jonas Harimana; Misozi Makangila; Jhonnah Mundike; Kakoma Kenneth Maseka (Scientific African)
Mine slag dumps could be point-sources of possible pollutants to the surrounding water and soils. The purpose of this study was to investigate the leaching behavior of zinc, lead and nickel from Nkana copper slag dump of Kitwe in Zambia. To assess the toxicity and hazardous nature of the slag, Bath Leaching EN 12,457–2:2002, Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP) were employed. The results from these techniques revealed that the copper slag was inert in the open or natural environment. Sequential extraction analysis was conducted to analyze the fractionation of the zinc, lead and nickel using a seven-step procedure. The sequential extraction analysis showed that the 3 metals were predominantly present in the residual fraction. The risk assessment code (RAC) showed that zinc and lead's mobility could pose an environmental risk categorized as low risk, with RAC values of 1.31 % and 1.50 %, respectively. Nickel's mobility fell within the no-risk category with a RAC of 0.32 %. Additionally, the effect of pH, particle size and contact time on the release of the 3 metals were investigated. The results showed that the highest concentrations of zinc and nickel were observed for longer period of exposure (>33 days), in acidic environments (pH 2.2 and pH 3.0), for particle size distribution (<75 μm). However, lead leaching was not affected by the variation of pH or particle size distribution but mostly by duration of exposure. X-ray diffraction (XRD) analysis revealed that diopside (CaMgSi2O6) and quartz (SiO2) constitute the primary phases within the sample. It is recommended to limit the exposure of slag material to acidic environments and minimize the fragmentation of the slag into finer particles as these conditions would promote increased release of zinc, lead and nickel to the surrounding environment.